Future Schools ( Modern Schools) - Xushnazavovich, Qurbanov Ravshan (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article we will talk about a new look at the space planning decisions of such institutions based on the typological requirements for the design of modern secondary schools and the organization of modern urban development and educational work. The purpose of the study is to analyze the principles and recommendations of the formation of architecture and planning of secondary schools in line with the specific characteristics of the modern educational process. Issues of architectural planning and formation of functional solutions of school buildings based on the search for new approaches in the design have been considered. In the development of a new spatial organization of the school environment, an analysis of the modern system of the educational process and its requirements is carried out. In addition, there is an opinion that the existing educational structure in modern schools, in the future, will change the design effect and architectural quality.